2017
DOI: 10.1109/ted.2017.2694440
|View full text |Cite
|
Sign up to set email alerts
|

A Vacancy-Interstitial Defect Pair Model for Positive-Bias Temperature Stress-Induced Electron Trapping Transformation in the High- $\kappa $ Gate n-MOSFET

Abstract: A vacancy-interstitial defect pair model for positive-bias temperature stress-induced electron trapping transformation in the high-κ gate n-MOSFET

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…5,21 Meanwhile, first-principles simulation, as one of the most effective and precise methods to investigate the specific defect characteristics in the material, is also extensively implemented in the BTI study. [22][23][24] A plethora of modeling and simulation works are performed to investigate the V O characteristics under the PBTI stress. The results obtained from these studies support the inference that V O is a shallow electron trap center and could be an effective electron capturing point under the PBTI stress.…”
Section: Introductionmentioning
confidence: 99%
“…5,21 Meanwhile, first-principles simulation, as one of the most effective and precise methods to investigate the specific defect characteristics in the material, is also extensively implemented in the BTI study. [22][23][24] A plethora of modeling and simulation works are performed to investigate the V O characteristics under the PBTI stress. The results obtained from these studies support the inference that V O is a shallow electron trap center and could be an effective electron capturing point under the PBTI stress.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Gao et al [56] reported that the electron detrapping is relatively constant and independent of the dynamic PBTI stress/relax cycle at the low oxide field of 5. that distinct defects are active under PBTI [56]. These experimental results exhibiting shallow-to-deep electron-trapping transformation under PBTI stressing were explained by Gu et al using a vacancy-interstitial (V O -O i ) defect pair model [135]. In this model, a V O -O i defect pair may evolve into a more stable state, with O i migrating from its original location to a different lattice vacancy position, marked by a substantial reduction in the system energy at the end of the O i migrating process and corresponding to an electron-trap state shifting from a shallow to a deeper energy level.…”
Section: R and P Components Under Pbtimentioning
confidence: 78%